A new species of torrent catfish, Liobagrus hyeongsanensis (Teleostei: Siluriformes: Amblycipitidae), from Korea - Kim, Su-Hwan; Kim, Hyeong-Su; Park, Jong-Young (Zootaxa, 2015)
A new species of torrent catfish, Liobargus hyeongsanensis, is described from rivers and tributaries of the southeastern coast of Korea. The new species can be differentiated from its congeners by the following characteristics: a small size with a maximum standard length (SL) of 90 mm; body and fins entirely brownish-yellow without distinct markings; a relatively short pectoral spine (3.7–6.5 % SL); a reduced body-width at pectoral-fin base (15.5–17.9 % SL); 50–54 caudal-fin rays; 6–8 gill rakers; 2–3 (mostly 3) serrations on pectoral fin; 60–110 eggs per gravid female.